2012
DOI: 10.1007/978-3-642-33442-9_21
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Code Forking and Sustainability in Open Source Software

Abstract: Abstract. The ability to create high-quality software artifacts that are usable over time is one of the essential requirements of the software business. In such a setting, open source software offers excellent opportunities for sustainability. In particular, safeguarding mechanisms against planned obsolescence by any single actor are built into the definition of open source. The most powerful of these mechanisms is the ability to fork the project. In this paper we argue that the possibility to fork serves as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
0
28
0
2
Order By: Relevance
“…The disagreements within blockchain communities often lead to a technical event known as a fork, which refers to the divergence of a blockchain into two or more potential paths [26]. For example, Bitcoin Cash (BCH) was created as a result of a successful fork from Bitcoin (BTC) due to the disagreement among the communities on increasing the block size.…”
Section: Introductionmentioning
confidence: 99%
“…The disagreements within blockchain communities often lead to a technical event known as a fork, which refers to the divergence of a blockchain into two or more potential paths [26]. For example, Bitcoin Cash (BCH) was created as a result of a successful fork from Bitcoin (BTC) due to the disagreement among the communities on increasing the block size.…”
Section: Introductionmentioning
confidence: 99%
“…From the governance perspective, code forks manifest a challenge (von Krogh and von Hippel 2006) or a failure of cooperation (Viseur 2012), calling for stronger leadership (Fleming and Waguespack 2007). Another, and smaller, stream of research views forking as a means to create derivative works and portrays it positively because it improves the long-term sustainability of the codebase (Gamalielsson and Lundell 2014, Nyman et al 2012, Nyman and Lindman 2013. In our study, we combine the technical perspective of forking with the competitive and strategic intent and define platform forking as a process that creates two competing platforms from the same resource base, and which are controlled by different and competing hosts.…”
Section: Platform Forkingmentioning
confidence: 99%
“…In this study, we found that inter-project forking is driven by organization strategy and policy. Previous studies found that the main reasons open source projects fork are technical variation, discontinuation of original project, community-driven, sustainability and legal issues [17,19]. Similar to open source projects, forks are used to divide work into di↵erent organizational teams and to deal with technical variations.…”
Section: Forking and Coordination In Multi Platform Developmentmentioning
confidence: 99%